NASIONALISME DAN PEMBENTUKAN NEGARA ISLAM DI PAKISTAN - Aisyah A Aisyah A (Sulesana: Jurnal Wawasan Keislaman, 2012)
This article explores the issue of the establishment of Pakistan as an Islamic state. Its political process was initiated after the independence of India when the Indian governmental system was based on constitution which ignored the multi-ethnic and muti-religious community in India. Muslims as minority group in India at that time felt ignored and did not play significant role in the state government. After the world war I, political consolidation and movement to establish an Islamic state had been initiated by uniting support from Muslim leaders to form Indial Muslim League. The struggle to establish a new Islamic state was not in vain. Pakistan was a name to the new state with Islamic concepts as the main reference in governing its society. This new Islamic state, later on, dismissed the word ‘Islam’ and needed further rational and liberal redefinition on what the country should be led to.